"I was right there": Explicating the relationship between trauma, history, and the body. Issue 177 (22nd April 2022) - Okello, Wilson Kwamogi
Abstract: If trauma is always "right there" for Black people, educators and practitioners must wrestle with the compounding nature of history, the body, and trauma that manifests in students' nuanced and analogous experiences. In the wake of increasing access to public acts of terror and violence, this article explicates the trauma‐body‐history relationship in relation to anti‐Blackness and offers some implications in the service of Black student's healing and survival.